Identification of miRNAs Involving Potato-Phytophthora infestans Interaction - Ming Luo; Xinyuan Sun; Meng Xu; Zhendong Tian (Plants, 2023)
sRNAs (small RNAs) play an important role in regulation of plant immunity against a variety of pathogens. In this study, sRNA sequencing analysis was performed to identify miRNAs (microRNAs) during the interaction of potato and Phytophthora infestans. Totally, 171 potato miRNAs were identified, 43 of which were annotated in the miRNA database and 128 were assigned as novel miRNAs in this study. Those potato miRNAs may target 878 potato genes and half of them encode resistance proteins. Fifty-three potato miRNAs may target 194 P. infestans genes. Three potato miRNAs (novel 72, 133, and 140) were predicted to have targets only in the P. infestans genome. miRNAs transient expression and P. infestans inoculation assay showed that miR396, miR166, miR6149-5P, novel133, or novel140 promoted P. infestans colonization, while miR394 inhibited colonization on Nicotiana benthamiana leaves. An artificial miRNA target (amiRNA) degradation experiment demonstrated that miR394 could target both potato gene (PGSC0003DMG400034305) and P. infestans genes. miR396 targets the multicystatin gene (PGSC0003DMG400026899) and miR6149-5p could shear the galactose oxidase F-box protein gene CPR30 (PGSC0003DMG400021641). This study provides new information on the aspect of cross-kingdom immune regulation in potato-P. infestans interaction at the sRNAs regulation level.